2017
DOI: 10.21037/atm.2017.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-guided antibiotic therapy—strengths and limitations

Abstract: Biomarkers as C-reactive protein (CRP) and procalcitonin (PCT) emerged as tools to help clinicians to diagnose infection and to properly initiate and define the duration of antibiotic therapy. Several randomized controlled trials, including adult critically ill patients, showed that PCT-guided antibiotic stewardship was repeatedly associated with a decrease in the duration of antibiotic therapy with no apparent harm. There are however some relevant limitations in these trials namely the low rate of compliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 52 publications
(60 reference statements)
0
42
0
6
Order By: Relevance
“…Given the benefits offered by the rational use of antibiotics, including the reduction of multiresistant bacteria 5,29,30 , treatment costs 31 , frequency of adverse effects 32 , and less interference with microbiome, objective criteria to define the ideal treatment length is warranted. CRP is a low-cost and affordable biomarker 10 , routinely used in intensive care, that has been shown relate to prognosis in studies involving different populations with serious infectious conditions 17,20,33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the benefits offered by the rational use of antibiotics, including the reduction of multiresistant bacteria 5,29,30 , treatment costs 31 , frequency of adverse effects 32 , and less interference with microbiome, objective criteria to define the ideal treatment length is warranted. CRP is a low-cost and affordable biomarker 10 , routinely used in intensive care, that has been shown relate to prognosis in studies involving different populations with serious infectious conditions 17,20,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…One useful marker is procalcitonin (PCT), whose benefit in reducing antibiotic treatment time was demonstrated in several studies 11,12,13,14,15,16 , including a potential reduction in the mortality of critically ill patients 14,15,16 . Nevertheless, the high cost of PCT testing reduces its availability in some settings 10,17 . In this context, C-reactive protein (CRP) may be an reasonable lowcost alternative 10,16,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available assays for CRP measurement are reliable, stable, reproducible, rapid, inexpensive, and present an acceptable limit of detection (0.3-5 mg/L). CRP has been analyzed in multiple clinical contexts, but only a small number of studies have focused on its use for optimizing antibiotic therapy [119]. In primary care, CRP improves the assessment of the severity of infection and extent of inflammation [120] and performs better in predicting the diagnosis of pneumonia than any individual or combination of clinical signs and symptoms.…”
Section: Developing New Antimicrobial Agents Increasing Antimicrobialmentioning
confidence: 99%
“…Serum biomarkers, particularly C-reactive protein and procalcitonin (PCT), have been examined as guides for both the initiation and discontinuation of antibiotics. While the data are inconsistent regarding the clinical utility of these biomarkers [15], procalcitonin levels may help inform decisions to de-escalate antibiotic therapy. In subgroup analyses of the PRORATA trial, investigators found that patients with ventilator-associated pneumonia assigned to the study arm (where antibiotics were discontinued after PCT levels reached <0.5 μg) had 3.1 fewer days (95% CI 0.7 days-5.6 days) of antibiotics than those patients assigned to the control arm, without a difference in mortality [16].…”
Section: Rapidly De-escalate Antimicrobial Therapymentioning
confidence: 99%